ANALISIS PRINSIP DISAIN CAHAYA ALAMI PADA BANGUNAN BERMASSA ( Kasus Studi : Sekolah Taruna Bakti Bandung ) - Taufik Arfan (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2011)
At certain buildings, such as educational building, conservation and efficiency of energy in order to create building that environmental friendly is very important. One of the method to minimized the needs of additional energy in buildings is through the exploitation of natural light. In addition to energy conser-vation function, the exploitation of natural light is also function as to create comfort in educational building at tropical area. Main method that was used in this thesis was through literature study about natural lighting and direct survey to collect data on the field of selected case, that was school building of Taruna Bhakti in Bandung. While, the final result of this process was redesign of the building at certain points which diagnosed have natural lighting problems. Based on the analysis result of literatur study about natural lighting in building, this thesis resulting three scales of discussion, that was environmental scale, building scale and interior scale. This division of scale was used to analyzed building’s condition so that the weakness could be orderly analyzed and design solution could be proposed. In general, based on building’s condition analysis on the study case, at several parts of the buildings was proposed redesigning of building’s elements at environmental scale, building scale, and interior scale. This redesign of the building was in form of exploration on the use of natural light so that every space in the school environment will have good natural lighting. Keyword: Natural Light, Energy Conservation, Comfort